Data on the relationship between acetone, ethylene glycol, isopropanol, methanol, and propylene glycol serum/plasma concentrations and osmolal gaps in patients at an academic medical center - Greene, Heather R. (Data Brief, 2020)
Ingestion of toxic alcohols other than ethanol (ethylene glycol, methanol, isopropanol, and propylene glycol) can cause life-threatening complications including altered level of consciousness, respiratory depression, and organ damage from metabolites. Many hospitals lack the ability to specifically analyze these compounds using gas chromatography, gas chromatography/mass spectrometry, or by enzymatic assays for ethylene glycol. Consequently, the presence of these compounds in blood is often ascertained indirectly by laboratory testing for acid-base status, osmolal gap, and anion gap. In the related research article, we analyzed 260 samples originating from 158 unique patients that had osmolal gap and specific testing for toxic alcohols performed on serum/plasma at an academic medical center central clinical laboratory. The data in this article provide the patient demographic, osmolal gap (and associated laboratory tests needed for this calculation), ethanol concentration by enzymatic assay, specific testing for toxic alcohols (ethylene glycol, isopropanol, methanol, propylene glycol) and acetone, anion gap, clinical history, antidotal treatment, and estimated timing of ingestion. The analyzed data is provided in the supplementary tables included in this article. Bias plots of osmolal gap estimations are included in a figure. The dataset reported is related to the research article entitled “Correlation of Osmolal Gap with Measured Concentrations of Acetone, Ethylene Glycol, Isopropanol, Methanol, and Propylene Glycol in Patients at an Academic Medical Center” [1].